Using micro-morphological fruit characters in resolving some of ambiguities in Iranian Acer L. (Sapindaceae) species - FATEMEH ASADI; FARIBA SHARIFNIA; FAHIMEH SALIMPOUR; AHMAD MAJD (Biodiversitas Journal of Biological Diversity, 2019)
Asadi F, Sharifnia F, Salimpour F, Majd A. 2019. Using micro-morphological fruit characters in resolving some of ambiguities in Iranian Acer L. (Sapindaceae) species. Biodiversitas 20: 297-304. Acer L. belongs to the Sapindaceae family consists of 126 species which are distributed in the temperate regions of the northern hemisphere. There are 12 taxa (including Acer monspessulanum with four subspecies and Acer velutinum with two varieties) in Iran. In this study 21 fruit characteristics are partially investigated using Scanning Electron Microscope (SEM) and Stereomicroscope. According to the obtained results, four types of faveolate, folded, wrinkled and pavement wing surface ornamentations as well as four types of faveolate, folded, verrucous, and wrinkled achene surface ornamentations were observed. Hair of wing margin, achene hair, wing ornamentation, inside angle of wing, and outside angle of wing have taxonomic value. According to fruit morphology, separation of 4 subspecies of A. monspessulanum can be verified. Also varieties of A. velutinum var. velutinum, and A. velutinum var. glabrescens were totally separated due to differences in characteristics such as wing ornamentation, achene ornamentation, hair density of achene, wing length, wing width, the ratio of length to width of wing, total fruit length, total fruit width, the ratio of length to width of fruit, inside angle of wing, outside angle of wing. The results showed that micro-morphological fruit characters of Acer genus are valuable in terms of taxonomy and classification of subspecies level.